2007
DOI: 10.1002/ejic.200600772
|View full text |Cite
|
Sign up to set email alerts
|

Catechol‐Bearing Dipyrazinylpyridine Complexes of Ruthenium(II)

Abstract: The new tridentate ligand 4-(3,4-methylenedioxyphenyl)-2,6-dipyrazinylpyridine (2) was prepared in good yield in a one-pot reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…[2,14] In this work, we used a one-pot synthesis of H1 at room temperature from 2-acetylpyridine and 4-carboxybenzaldehyde (the ethyl ester of which can be used just as well) in the presence of KOH and NH 4 OH in aqueous MeOH (Scheme 1), a process that we have previously used to prepare several 4Ј-substituted terpyridines and dipyrazinylpyri-dines. [9,10,16,17] This precipitates a salt form which, after redissolving, was acidified to precipitate analytically pure H1 in 80 % yield. The free ligand lacking the spacer, terpyridine-4Ј-carboxylic acid H2, was first isolated as an unintended byproduct of a convergent preparation of its ethyl ester by Stille coupling, in 4 steps and 28 % overall yield from commercial citrazinic acid.…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…[2,14] In this work, we used a one-pot synthesis of H1 at room temperature from 2-acetylpyridine and 4-carboxybenzaldehyde (the ethyl ester of which can be used just as well) in the presence of KOH and NH 4 OH in aqueous MeOH (Scheme 1), a process that we have previously used to prepare several 4Ј-substituted terpyridines and dipyrazinylpyri-dines. [9,10,16,17] This precipitates a salt form which, after redissolving, was acidified to precipitate analytically pure H1 in 80 % yield. The free ligand lacking the spacer, terpyridine-4Ј-carboxylic acid H2, was first isolated as an unintended byproduct of a convergent preparation of its ethyl ester by Stille coupling, in 4 steps and 28 % overall yield from commercial citrazinic acid.…”
Section: Synthesismentioning
confidence: 99%
“…[6,7] Pyrazine-containing ligands have long been known, [8] but the first dipyrazinylpyridine (dpp) was reported in 2001, [9] and we found that its homoleptic Ru II complex showed a longer excited-state lifetime than its terpyridine analogue and faster rates of photoinduced electron transfer in homogeneous solution. [10] This was attributed mainly to the presence of the additional nitrogen atoms. The electron injections from photoexcited states into a conduction band of a semiconductor have been found to be extremely rapid (femtosecond timescale), [11] and this would seem to diminish the importance of the excited-state lifetime.…”
Section: Introductionmentioning
confidence: 98%
“…The absorption maximum at 293 nm corresponds to an n → π* transition. 67,84,85 The addition of one equiv. of aqueous CuCl 2 (1 mM, 60 μL) to the solution of L (200 μM, 300 μL) in aqueous acetonitrile (2 mL, 4 : 1 v/v, 10 mM HEPES buffer, pH 7.4) resulted in the appearance of a new absorption band at 350 nm (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Another series of bis-tridentate complexes was reported in 2007 by Al-mutlaq et al [ 137 ] using dipyrazinyl-pyridine ligands with different substituents on 4’- position, and cathecol moieties as grafting groups ( 41 , Figure 31 ). In comparison to homolog complexes with terpyridine, dipyrazinyl-pyridine led to higher oxidation potential.…”
Section: Modifications Of Black Dye and Structure-properties Relatmentioning
confidence: 99%